Comeback is Real - Ahmad, Mohd Hanafiah (Penerbit Universiti Malaysia Pahang, 2021)
"I do not know how to deal with your case. If there is no solution, then you will have to face the termination process by your university". That was the words that came out of from the Vice Chancellor during his meeting with the staff who have not completed their PhD studies in 2013. I know that the university has helped me all this time, and I do not see how the university can help me in this situation. I know, the implications were huge, and I must face all the possibilities after this. Here is my story ...